METHODICAL BASES OF TEACHING HIGHER MATHEMATICS BY THE ELECTRONIC TEXTBOOK (Journal of Information Technologies in Education (ITE), 2011)
This work examines principle of systematization, structurization and visualization of the academic material in the higher mathematics by means of structurally-logical charts. Bases of teaching method of students is offered by the electronic textbook, which contains the text of the academic material, package of proper it structurally-logical charts of different level of working out in detail, and also some tasks of the professional orientation.
Keywords: electronic textbook; higher mathematics; navigation; structurally-logical chart